Barrier to Adoption of Integration of Maize-Livestock in Maros, Gowa and Takalar Regency - S. Baba; S. N. Sirajuddin; A. Abdullah; M. Aminawar (Jurnal Ilmu dan Teknologi Peternakan, 2014)
The advantage of integration of corn and cattle has been promoted through demonstration plot and other extension ways. However, the rate of its adoption is still low and not widely accepted. The purpose of this study was to explore the factors that thwort of farmers from adopting the corn and cattle integration system. Survey method was used in this research and was conducted at Maros (glatinous corn production centre), Gowa district (Sweet corn production centre) and Takalar district (yellow and sweet corn production centre). Data collection were carried out using delphie method with three stages. First stage was to explore the factors that thwort of farmer from adopting the technology using FGD.  FGDs were conducted with key informants such as farmers who plant corn and cattle and extension agents.  Second and third stages were to reduce the factors into five most important factors.  The result showed that the inhibiting factor in adopting utilization of corn stalk for animal feeding in Maros regency was lack of feed storehouse, in Takalar Regency was the lack of knowledge in preserving corn stalk and in Gowa was the availability of many other feed resources.  The barrier to adoption of the use of manure as organic fertilizer was the lack of knowledge in composting (in Gowa and Takalar) and the cost of manure processing (in Maros).